Basic business communication : - Lesikar, Raymond V. (McGraw - Hill, 2005)
Basic Business Communication (BBC), 10/e by Lesikar and Flatley provides both student and instructor with all the tools needed to navigate through the complexity of the modern business communication environment. At their disposal, teachers have access to an online Tools & Techniques Newsletter that will continually keep them abreast of the latest research and developments in the field while providing a host of teaching materials. Exciting new student resources, including a subscription to the Merriam Webster Collegiate website and an enhanced CD-ROM, allow students to practice and master concepts in fun and interesting ways. BBC attends to the dynamic, fast-paced, and ever-changing means by which business communication occurs by being the most technologically current and pedagogically effective books in the field. It has realistic examples that are both consumer-and business-oriented.